Israel’s Prophets Meet Athens’ Philosophers: Scriptural Echoes in Acts 17,22-31 - Litwak, Kenneth D. (Biblica, 2004)
Generally, treatments of Paul’s speech note biblical parallels to Paul’s wording but find no further significance to these biblical allusions. This study argues that Luke intends far more through this use of the Scriptures of Israel beyond merely providing sources for Paul’s language. I contend that, through the narrative technique of "framing in discourse", Luke uses the Scriptures of Israel to lead his audience to interpret Paul’s speech as standing in continuity with anti-idol polemic of Israel’s prophets in the past. As such, read as historiography, Luke’s narrative uses this continuity to legitimate Paul’s message and by implication, the faith of Luke’s audience. Luke’s use of the Scriptures here is ecclesiological.